2007
DOI: 10.1038/sj.npp.1301634
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to Repeated Morphine Administration Is Associated with Increased Potency of Opioid Agonists

Abstract: Tolerance to the pain-relieving effects of opiates limits their clinical use. Although morphine tolerance is associated with desensitization of m-opioid receptors, the underlying cellular mechanisms are not understood. One problem with the desensitization hypothesis is that acute morphine does not readily desensitize m-opioid receptors in many cell types. Given that neurons in the periaqueductal gray (PAG) contribute to morphine antinociception and tolerance, an understanding of desensitization in PAG neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 39 publications
(58 reference statements)
0
55
1
Order By: Relevance
“…This rapid recovery from desensitization could contribute to differences observed in the tolerance produced by intermittent versus continuous administration of morphine. In slices from rats that were treated intermittently with morphine, cellular tolerance in periaqueductal gray neurons was not only lost, but ME was actually more potent in inducing GIRK current (Ingram et al, 2008). Furthermore, intermittent morphine treatment causes less antinociceptive tolerance than continuous treatment (Dighe et al, 2009).…”
mentioning
confidence: 89%
“…This rapid recovery from desensitization could contribute to differences observed in the tolerance produced by intermittent versus continuous administration of morphine. In slices from rats that were treated intermittently with morphine, cellular tolerance in periaqueductal gray neurons was not only lost, but ME was actually more potent in inducing GIRK current (Ingram et al, 2008). Furthermore, intermittent morphine treatment causes less antinociceptive tolerance than continuous treatment (Dighe et al, 2009).…”
mentioning
confidence: 89%
“…Regions of codistribution included some cortical layers, the nucleus accumbens, the hippocampal formation, some nuclei of the amygdala, and the periaqueductal gray. Because neurons of the periaqueductal gray contribute to both the clinically beneficial antinociceptive effects of morphine and the clinically restricting development of tolerance (Bagley et al, 2005;Ingram et al, 2008), we explored whether heterologous coexpression of the 5-HT 2A and MOP receptors would result in their cross-regulation and alteration in the ability of morphine to desensitize or cause internalization of the MOP receptor.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed initially that the development of tolerance to morphine would reflect MOP receptor desensitization, which would be anticipated to preclude sustained function (Gainetdinov et al, 2004). Indeed, recent studies have suggested that repeated morphine administration can en-hance agonist potency and hence increase receptor desensitization and promote tolerance (Ingram et al, 2008). In contrast, a series of studies have suggested that tolerance to morphine may stem from a lack of rapid desensitization, resulting in other adaptive, and potentially slowly reversible, changes becoming dominant (for review, see Martini and Whistler, 2007).…”
mentioning
confidence: 99%
“…Desensitization induced by ME, DAMGO, and morphine (and methadone, Quillinan et al, 2011) are all more pronounced in locus coeruleus Williams, 2004, 2005), as well as in periaqueductal gray neurons (Ingram et al, 2008), after withdrawal from chronic exposure to morphine. Enhanced desensitization is one mechanism that would contribute to opioid tolerance.…”
Section: A Accelerated Desensitizationmentioning
confidence: 99%
“…Studies using physiologic end-points (direct Gbg interactions with ion channels) in single opioidsensitive neurons have also reported similar impaired MOR-effector coupling in a range of neuronal cell types from animals chronically treated with morphine in vivo, including rat and mouse periaqueductal gray (Bagley et al, 2005b;Ingram et al, 2008), rat and mouse locus coeruleus (Christie et al, 1987;Connor et al, 1999;Dang and Williams, 2004;Bailey et al, 2009a;Dang et al, 2011;Quillinan et al, 2011), and mouse trigeminal ganglion neurons (Johnson et al, 2005). Similar results have also been reported for inhibition of GABAergic synaptic transmission in nerve terminals in periqueductal gray taken from animals treated chronically with morphine (Fyfe et al, 2010;Hack et al, 2003).…”
Section: A Desensitization and Tolerance Are Both Associated With Rementioning
confidence: 99%